2000
DOI: 10.1001/archfami.9.9.843
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Health: Comparisons in the Women's Health Initiative Sample

Abstract: This sample of older lesbian and bisexual women from WHI shows many of the same health behaviors, demographic, and psychosocial risk factors reported in the literature for their younger counterparts, despite their higher socioeconomic status and access to health care. The lower rates of recommended screening services and higher prevalence of obesity, smoking, alcohol use, and lower intake of fruit and vegetables among these women compared with heterosexual women indicate unmet needs that require effective inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
255
1
9

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(277 citation statements)
references
References 43 publications
12
255
1
9
Order By: Relevance
“…All were from high‐income countries (five USA, two UK, and one each from Canada, Belgium, Denmark and Sweden). Sizes ranged from 3129 to 91 582 participants 11. Recruitment methods varied, and included clinic, convenience and population samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All were from high‐income countries (five USA, two UK, and one each from Canada, Belgium, Denmark and Sweden). Sizes ranged from 3129 to 91 582 participants 11. Recruitment methods varied, and included clinic, convenience and population samples.…”
Section: Resultsmentioning
confidence: 99%
“…These include increased tobacco and alcohol use,2, 3 higher body mass index (BMI),4, 5, 6 and reduced uptake of cervical cytology screening 7, 8, 9. Lesbians are also said to have fewer reproductive behaviours that are associated with protection from various reproductive system cancers than heterosexual women, including use of oral contraceptives, childbirth and breastfeeding 10, 11. Furthermore, there is a theory that lesbians have higher levels of testosterone, which could contribute to higher rates of polycystic ovary syndrome (PCOS) 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers are increasingly recognizing that breast cancer affects all women, regardless of sexual orientation or marital or partnership status. Compared to heterosexual women, sexual minority women, defined as self-identified lesbian and bisexual women and those who prefer female partners [16], may have greater breast cancer risk factors [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], incidence [32], and mortality [33]. Thus, the exclusive focus of most breast cancer survivorship and caregiving research on heterosexual women and dyads carries important implications for the generalizability and translational utility of research findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has suggested that lesbians and bisexual women are more likely to drink alcohol heavily and to smoke cigarettes than are heterosexual women, [1][2][3][4][5][6] whereas other research has showed no significant differences. [7][8][9][10][11][12][13] Research published before 2000 on the prevalence of alcohol consumption and cigarette smoking among lesbians and bisexual women was based primarily on small, homogeneous convenience samples recruited from the lesbian and bisexual communities, and the findings therefore have had limited generalizability.…”
mentioning
confidence: 99%